2023
DOI: 10.1007/s12144-023-04403-9
|View full text |Cite
|
Sign up to set email alerts
|

Online learning during the Covid-19 pandemic: How university students’ perceptions, engagement, and performance are related to their personal characteristics

Abstract: University students faced unexpected challenges in online learning during the Covid-19 pandemic. Findings from early phases of the Covid-19 pandemic and before show that online learning experiences may vary from student to student and depend on several personal characteristics. However, the relative importance of different students’ personal characteristics for their online learning experiences at later phases of the Covid-19 pandemic is still unclear. This cross-sectional, correlational study investigates how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…The COVID-19 pandemic has drastically affected the global educational system, including higher education ( Martin et al, 2022 ). Universities worldwide have embraced the online platform, which poses students with unprecedented challenges and ultimately elevates academic stress ( Kaspar et al, 2023 ). Academic stress, though, surfaces from the interaction of multiple factors ( García-Martínez et al, 2022 ); these factors substantially differ between regular and pandemic times.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has drastically affected the global educational system, including higher education ( Martin et al, 2022 ). Universities worldwide have embraced the online platform, which poses students with unprecedented challenges and ultimately elevates academic stress ( Kaspar et al, 2023 ). Academic stress, though, surfaces from the interaction of multiple factors ( García-Martínez et al, 2022 ); these factors substantially differ between regular and pandemic times.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that they were able to speed up their studying and developed more self-discipline and a sense of responsibility towards their learning. Studies have shown that adaptation to online learning during the pandemic period was subjected to contextual and personal variations and that some factors such as age, self-e cacy, and selfregulation skills play important roles in university students' level of adaptation [5,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, personal traits and individual variances can impact the effectiveness of online education. Kaspar et al (2023) found that personality factors, educational attainment, and gender all significantly affected the online learning outcomes of university students during the pandemic, while anxiety was found to moderate pre-service teachers' inclination to use digital technologies. Thus, individual circumstances may influence the success of online education.…”
Section: Challenges Of Online Learning For Pre-service Teachersmentioning
confidence: 96%
“…The literature review above indicates that positive online academic experiences for pre-service teachers require adaptation to new online platforms and technologies (Zheng et al, 2021). Personal traits and individual variances impact the effectiveness and quality of pre-service teachers' online education (Kaspar et al, 2023), which also require faculty to have a comprehensive understanding of pedagogical principles and the ability to create interactive and engaging learning experiences (Byrka et al, 2022). Understanding faculty's readiness and providing them with the required training and resources, along with effective assessment and feedback, are crucial for the transition to high-quality online teacher education programs (Cutri et al, 2020;Joshi et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%